Asuhan Keperawatan Pada Nn. S Dengan Gangguan Sistem Pencernaan : Abdominal Pain di Ruang Dahlia RSUD Dr. Soeselo Kabupaten Tegal - Syevita Yuliana Sari; Tati Karyawati; Sujono Sujono (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Abdominal pain is a general term for any symptom of a disease that affects the area between the chest and pelvis (abdominal wall) depending on the severity, duration and location of the pain. The purpose of this paper is to find out and provide nursing care for Ms. S with digestive system disorders: abdominal pain in the dahlia ward of dr. Soeselo hospital, Tegal Regency according to nursing standards. The data collection techniques in this scientific paper are in the form of interviews, observations, documentation studies and literature studies. From the case review, it was found that the client’s main complaint was abdominal pain in the upper left side, P: pasin when eating spicy food (pain decreases when lying down), Q: like being pressed, R: upper left abdomen quadrant 2, S: pain scale 5, T: continuous. The nursing problems found were acute pain, nausea and knowledge deficit. Interventions were arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and can be implemented.